Improved Rotor Flux-Based SMO and RBF-PID Control Strategy for PMSM - Weiyang Wang; Yongqing Liu; Huipeng Chen; Jian Gao; Shaopeng Zhu; Rougang Zhou (Actuators, 2023)
This paper proposes a control strategy that combines an improved flux-based sliding mode observer with a Radial Basis Function Proportional-Integral-Derivative (RBF-PID) controller for the control of Permanent Magnet Synchronous Motors (PMSM). The strategy aims to address the issues of electrical angle estimation errors and torque fluctuations in traditional sliding mode observer control. The improved sliding mode observer utilizes the flux model of the PMSM to enhance the accuracy of electrical angle estimation, thereby reducing the estimation errors and improving the control of the current loop and speed. The RBF-PID controller ensures system stability while achieving faster response and reduced torque fluctuations. Simulation and experimental results demonstrate that compared to traditional PI control and sliding mode observer control methods, the proposed strategy improves the performance of electrical angle estimation by 7.05% and reduces overshoot in the q-axis current by 28.6%, exhibiting better control performance and smaller errors.